A new method of metallurgical silicon purification - Maronchuk, I.E.; Solovyev, O.V.; Khlopyonova, I.A. (Functional Materials, 2005)
Studied have been individual purification stages of metallurgical silicon by recrystallization from the Ga-Si system melt followed by isolation and washing of crystals using chemical methods. The technological sequence for silicon purification has been developed. The method makes it possible to purify silicon containing at least 98.0% Si by weight. The subsequent purification by crystallization from the melt provides the product purity level up to 99.999 mass.%